Non-Western responses to terrorism - Boyle, Michael J. (New directions in terrorism studies, 2019)
This edited collection surveys how non-Western states have responded to the threats of domestic and international terrorism in ways consistent with and reflective of their broad historical, political, cultural and religious traditions. It presents a series of eighteen case studies of counterterrorism theory and practice in the non-Western world, including countries such as China, Japan, India, Pakistan, Egypt and Brazil. These case studies, written by country experts and drawing on original language sources, demonstrate the diversity of counter-terrorism theory and practice and illustrate how the world 'sees' and responds to terrorism is different from the way that the United States, the United Kingdom and many European governments do. This volume - the first ever comprehensive account of counter-terrorism in the non-Western world - will be of interest to students, scholars, students and policymakers responsible for developing counter-terrorism policy.